Quality Early Childhood Development centres: an exploratory study of stakeholder views - Clampett, Bridget (Department of Social Development, 2016)
This study 'Quality Early Childhood Development (ECD) centres: an exploratory study of stakeholder views' was carried out with a sample of fifteen principals of effective ECD centres in the Western Cape, South Africa. The study adopted a qualitative, exploratory approach using a semi-structured interview schedule for face-to-face interviews with the participants. A purposive sample was used and the selected sample were geographically spread across the Western Cape Metropolitan area.The findings revealed the following: Effective ECD centres that provide quality care and education is of critical importance and should be prioritised in South Africa. Governing bodies play critical roles in the effectiveness of ECD centres; these roles include: governance and accountability, ensuring financial sustainability, decision-making and administration, strategic planning, monitoring and evaluation, and conflict resolution. ECD forums are also a valuable asset for ECD centres. Structure and routine, indoor learning materials and the arrangement of the classroom are important components of quality learning programmes. Qualified ECD teachers provide quality learning programmes for children and outdoor play is important for children's holistic development. Parental involvement improves learning outcomes for children and relationships with stakeholder's assists centres in providing a holistic programme. Principals play a crucial role in ensuring a quality service is provided.